Placement and outreach of group-based credit organizations: the cases of ASA, BRAC, and PROSHIKA in Bangladesh - Sharma, Manohar; Zeller, Manfred (International Food Policy Research Institute, 1999)
Bangladesh has witnessed major strides in providing financial services to the rural poor. These services are provided largely through innovative group-based credit programs of several nongovernmental organizations. The implicit but widespread assumption has been that they are indeed placed in special poverty-stricken areas. Is this assumption valid? If not, what factors actually affect programs' placement across communities? This paper uses an unique thana-level data set to analyze the placement of three group-based credit programs in Bangladesh. Analysis of branch placement indicates that, unlike commercial banks, nongovernmental institutions do respond to general conditions of poverty. However, it appears that NGO services are located more in poor pockets of relatively well-developed areas than in remoter, less-developed regions. Client density of the established branches, however, did not exhibit such a feature and actually tended to be better in less advantageous locations.